The association between tricuspid regurgitation velocity and 5‐year survival in a North West London population of patients with sickle cell disease in the United Kingdom. (29th May 2013) - Zimbarra Cabrita, Inês; Mohammed, Abubakar; Layton, Mark; Ghorashian, Sara; Gilmore, Annette; Cho, Gavin; Howard, Jo; Anie, Kofi A.; Desforges, Lynda; Bassett, Paul; Grapsa, Julia; Howard, Luke; et al.
Summary: Raised tricuspid regurgitant velocity (TRV) occurs in approximately 30% of adults with sickle cell disease (SCD), and has been shown to be an independent risk factor for death. TRV was assessed in 164 SCD patients who were subsequently followed up for survival. Raised pulmonary pressures were defined as a TRV jet ≥2·5 m/s on echocardiography. Elevated TRV was present in 29·1% of patients and it was associated with increased age and left atrial diameter. There were 15 deaths (9·1%) over a median of 68·1 months follow up; seven patients had increased TRV, and eight patients had a TRV<2·5 m/s. Higher TRV values were associated with a greater than 4‐fold increased risk of death (Hazard Ratio: 4·48, 99% confidence interval 1·01‐19·8), although we found a lower overall mortality rate than has been reported in previous studies. TRV was not an independent risk factor for death. We have confirmed the association between raised TRV and mortality in a UK SCD population whose disease severity appears to be less than that reported in previous studies. Further prospective studies are needed to more clearly characterize which patient factors modify survival in SCD patients with raised TRV.